2015
DOI: 10.4254/wjh.v7.i9.1209
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese medicine for prevention and treatment of hepatocarcinoma: From bench to bedside

Abstract: and other TCM syndromes (Zheng). Modern treatments such as surgery, transarterial chemoembolization (TACE) and high intensity focus ultrasound treatment would influence the manifestation of TCM syndromes. Herbs with traditional efficacy of tonifying Qi, blood and Yin, soothing liver-Qi stagnation, clearing heat and detoxifying and dissolving stasis, have been demonstrated to be potent to prevent hepatocarcinogenesis. TCM has been widely used in all aspects of integrative therapy in hepatocarcinoma, including s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 116 publications
1
41
0
Order By: Relevance
“…It has previously been reported that the Dox-induced apoptotic mechanism is reactive oxygen species-dependent in normal cells and p53-dependent in cancer cells (39). In addition, SPPC, the extract of L. japonica, was shown to promote apoptosis by downregulating IL-10 expression (40). The present study demonstrated that SPPC reduced the viability of breast cancer cells and that, when used in combination with DOX, it was able to promote the apoptosis of breast cancer cells, while simultaneously reducing the dose and adverse effects of Dox.…”
Section: A B C Dmentioning
confidence: 99%
“…It has previously been reported that the Dox-induced apoptotic mechanism is reactive oxygen species-dependent in normal cells and p53-dependent in cancer cells (39). In addition, SPPC, the extract of L. japonica, was shown to promote apoptosis by downregulating IL-10 expression (40). The present study demonstrated that SPPC reduced the viability of breast cancer cells and that, when used in combination with DOX, it was able to promote the apoptosis of breast cancer cells, while simultaneously reducing the dose and adverse effects of Dox.…”
Section: A B C Dmentioning
confidence: 99%
“…In order to guarantee the validity and reliability, evidence-based preclinical and clinical explorations are required. Moreover, elucidation of the underlying pharmaceutical mechanism could bene t the acceptance of TCM application [12][13][14][33][34][35].…”
Section: Gjf Inhibited the Activation Of Mitosis-related Protein Of Hmentioning
confidence: 99%
“…Recent studies have indicated that TCM can induce cell-cycle arrest and attenuate the tumor-associated macrophage-stimulated proliferation to inhibit tumor proliferation [12][13][14]. In addition, more and more researches con rmed the synergism and detoxi cation of combination of TCM with chemo-or radiotherapy [15].…”
Section: Introductionmentioning
confidence: 99%
“…During this period, the treatment options for HCC have expanded to include additional chemotherapeutic agents and targeted therapies (21,22). In recent years, traditional Chinese medicine (TCM), or its extractions, have had a positive role in the treatment of cancer (23,24).…”
Section: Introductionmentioning
confidence: 99%